Attachment and spreading of human embryonal carcinoma stem cells on nanosurfaces monitored by optical waveguides - Aref, Amirreza; Horvath, R.; Ansari, Farahnaz; Ramsden, Jeremy J. (Cranfield University, 2008)
Cell adhesion is an active process, carried out in vivo via receptor ligand-like interactions between cell surface adhesion molecules and the extracellular matrix. Initial cell surface reactions following contact may trigger multiple responses, which in tum result in either spreading or detachment of the cell. The set of adhesion and attachment molecules mediating the adhesive behaviour of stem cells and the kinetics of their interactions are as yet largely unknown. In this paper we have investigated the attachment and spreading kinetics of human embryonal carcinoma stem cells (TERA2.sp12) onto the planar Si(Ti)O2 waveguides, and covered with poly-L-lysine (PLL) or mucin, acting as substrata for the cells.